Screw and cement augmentation of tibial defects in primary total knee arthroplasty: satisfactory midterm outcomes. Issue 3 (14th May 2018) - Gaudin, Gael; Butcher, Chris; Lustig, Sebastien; Darwish, Nader; Neyret, Philippe
Abstract : Objective: There are several options for dealing with tibial bone defects during total knee arthroplasty (TKA) in severe primary osteoarthritis. The aim of this study was to report the midterm results of TKA with screw and cement augmentation of moderate-sized tibial bone defects. Methods: Patients with osteoarthritis who had posterior stabilised TKA with screw and cement augmentation of the tibia were reviewed retrospectively. Patients were assessed preoperatively and at follow-up using the International Knee Society Knee Score (KS) and Function Score (FS), and radiographic analysis of alignment and signs of loosening. Results: Twenty knees in 19 patients were included in the study. The mean age was 71 years; mean follow-up was 58 months. KS improved from 46 to 76 and FS from 51 to 92. The femorotibial mechanical angle changed from 174 to 178. There were no signs of osteolysis or loosening, and no revisions. Radiolucent lines at the cement bone interface were common but non-progressive. Conclusions: Midterm clinical and radiographic results of TKA with screw and cement augmentation for moderate tibial defects were satisfactory. Level of evidence: V.